LOCAL GOVERNMENT CAPACITY IN SUSTAINABLE TOURISM DEVELOPMENT - M. Rafi; Rosti Novriana (Jurnal Kebijakan Publik, 2024)
The existence of problems related to the government's lack of capability to develop tourist attractions has caused a drastic decline in the number of visitors to the Artificial Lake tourist attraction and requires policy improvements by all stakeholders. This research aims to determine the capabilities of the Culture and Tourism Department in developing the Artificial Lake tourist attraction in Pekanbaru City. This research uses a qualitative research method with a descriptive approach, where data collection procedures include interviews and documentation. Meanwhile, the data analysis technique uses Nvivo 12 Plus software as a qualitative research tool that can analyze data with critical combinations using the crosstab query analysis feature. The findings of this research indicate that the Pekanbaru City Culture and Tourism Office has a work program in the knowledge and skills dimension, but the existing work program is not specifically directed at the process of developing the Artificial Lake tourist attraction. Then, from the technical system dimension, the Culture and Tourism Service currently does not have adequate standard operating procedures (SOP) and information systems for the development of the Artificial Lake tourist attraction. Next, in the managerial system dimension, the Culture and Tourism Service has collaborated with PT. Pekanbaru Development Facilities, but the budgeted program planning has not yet been implemented, and there has been no further coordination for the development of the Artificial Lake tourist attraction. Furthermore, the absence of a specific motto vision, and mission for Artificial Lake tourism in the development process has shown a lack of seriousness and capability of the local government in the dimensions of values and norms regarding the Artificial Lake tourist attraction development project. Based on these conditions, this study contributes to encouraging the improvement of local government capabilities in systematically managing sustainable tourism development in each core capability dimension.